ANALYSIS OF THE EXISTENCE OF ELEMENTS OF GHARAR AND TADLIS IN CUTTING THE WEIGHT OF THE SCALES - Faisal Yahya; Rizki, Muhammad (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2023)
This research aims to find out how the mechanism of cutting scales in buying and selling chili peppers, and how to analyze the existence of elements of gharar and tadlis in the practice of cutting scales in buying and selling chili peppers. This research uses normative-empirical legal research with descriptive analysis. The data comes from primary data obtained from the field and secondary data obtained from literature research. The results showed that the implementation mechanism for cutting the weight of the scales in the sale and purchase of chili peppers that took place was practiced according to the customs prevailing in the community of Gampong Abo Teubeng. This sale and purchase is carried out with the application of mandatory deductions at the time after weighing. Weighing pieces in this transaction range from 0.5-2kg depending on the size of the sack used by the farmer. If blue line sacks are used, the weight cut ranges from 1-2kg and fertilizer sacks with weight cuts range from 0.5-1kg. The weight cut is also influenced by market prices, if the market price is expensive then the cut will be small, if the price is cheap the cut will be large. Second, according to the review of muamalah fiqh, the existence of elements of gharar and tadlis in the transaction of cutting the weight of the scales in the sale and purchase of chili in Gampong Abo Teubeng shows that there is an element of gharar in the transaction, but the element of gharar is forgiven because it is included in mild gharar. Because the risk of heavy shrinkage is something that cannot be separated from the transaction. The existence of the element of tadlis in the transaction is visibly absent because of the willingness of both parties. However, invisibly it may not be because it is up to the buyer's intention. If they intend to gain more profit from the cut in the scales then it falls into tadlis. And if he does not intend to gain more profit then it is not included because it is in the pleasure of both parties when dealing.